2014
DOI: 10.1159/000368903
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide as Palliative Treatment in Patients with Advanced Secondary Glioblastoma

Abstract: Background: For its numerous abilities including sedation, we have been using thalidomide (TH) as the ‘last therapeutic option' in patients with advanced gliomas. We noticed that a small subgroup, i.e. patients with secondary glioblastoma (GBM, whose GBM has evolved over several months or years from a less malignant glioma), survived for prolonged periods. Therefore, we retrospectively evaluated the outcomes of patients with secondary GBM treated with TH at our centre. Patients and Methods: Starting in the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Among them, afatinib and dacomitinib were approved by the FDA. In 2015, a phase I/phase II study regarding afa- Imatinib showed no significant changes in the HGGs and especially GBM tumor growth [46] Better results were obtained in combination with hydroxyurea [47] Tandutinib had little effect [ Vatalanib enhances the antiangiogenic activity [54] Disappointing results were obtained for pazopanib in combination with lapatinib [57] No promising activity for GBM patients treated with sunitinib [58] Cediranib is an inhibitor of VEGFR, PDGFR, and c-kit [59] Thalidomide had a good effect as palliative drug in advanced secondary glioblastoma [60] Cabozantinib had good results both in vitro and in clinical trials [61,62] SU1498 had a limited anti-tumor activity [51] EGFR -epidermal growth factor receptor, PDGFR -platelet-derived growth factor receptor, IGF-R -insulin-like growth factor receptor, VEGFR -vascular endothelial growth factor receptor, FDA -Food and Drug Administration, ERK -extracellular signal-regulated kinases, HGGs -high-grade gliomas, GBs -glioblastomas, c-kittransmembrane tyrosine kinase receptor tinib alone or in combination with temozolomide proved that the drug was safe but with limited activity [37]. Also, single-agent dacomitinib proved to have limited activity in a phase II clinical trial in recurrent glioblastoma patients with EGFR amplification [38], following preclinical studies with good results [39].…”
Section: Receptor Tyrosine Kinase Inhibitors For Glioblastoma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, afatinib and dacomitinib were approved by the FDA. In 2015, a phase I/phase II study regarding afa- Imatinib showed no significant changes in the HGGs and especially GBM tumor growth [46] Better results were obtained in combination with hydroxyurea [47] Tandutinib had little effect [ Vatalanib enhances the antiangiogenic activity [54] Disappointing results were obtained for pazopanib in combination with lapatinib [57] No promising activity for GBM patients treated with sunitinib [58] Cediranib is an inhibitor of VEGFR, PDGFR, and c-kit [59] Thalidomide had a good effect as palliative drug in advanced secondary glioblastoma [60] Cabozantinib had good results both in vitro and in clinical trials [61,62] SU1498 had a limited anti-tumor activity [51] EGFR -epidermal growth factor receptor, PDGFR -platelet-derived growth factor receptor, IGF-R -insulin-like growth factor receptor, VEGFR -vascular endothelial growth factor receptor, FDA -Food and Drug Administration, ERK -extracellular signal-regulated kinases, HGGs -high-grade gliomas, GBs -glioblastomas, c-kittransmembrane tyrosine kinase receptor tinib alone or in combination with temozolomide proved that the drug was safe but with limited activity [37]. Also, single-agent dacomitinib proved to have limited activity in a phase II clinical trial in recurrent glioblastoma patients with EGFR amplification [38], following preclinical studies with good results [39].…”
Section: Receptor Tyrosine Kinase Inhibitors For Glioblastoma Treatmentmentioning
confidence: 99%
“…Another antiangiogenic agent which proved good effects on GB patients is thalidomide. The drug had a good effect when used as a palliative drug for patients with advanced secondary GB [60]. SU1498 is a VEGFR inhibitor that proved to have a cytotoxic effect on GB9B cells.…”
Section: Receptor Tyrosine Kinase Inhibitors For Glioblastoma Treatmentmentioning
confidence: 99%
“…The mechanism of anti-angiogenic action is not fully known [40]. Its use has been investigated in the care of high-grade glioma [41].…”
Section: Thalidomidementioning
confidence: 99%
“…While their mechanism of action is not entirely elucidated, they seem to exert their immunomodulatory and antiangiogenic properties via inhibition of TNF, interleukin–6, IgG, and VEGF; costimulation of T cells and NK cells; and increased interferon–gamma and interleukin–2 . Thalidomide has been tested in adults with newly diagnosed and relapsed glioblastoma . Additionally, pomalidomide has been evaluated in a phase II trial for children with relapsed/refractory brain tumors (NCT03257631), and although it did not show clinically meaningful antitumor efficacy as single agent, sustained responses in children with HGG have been reported …”
Section: Immunotherapeutic and Immunomodulatory Agents In Phggmentioning
confidence: 99%
“…[82][83][84] Thalidomide has been tested in adults with newly diagnosed and relapsed glioblastoma. [85][86][87] Additionally, pomalidomide has been evaluated in a phase II trial for children with relapsed/refractory brain tumors (NCT03257631), and although it did not show clinically meaningful antitumor efficacy as single agent, sustained responses in children with HGG have been reported. 88…”
Section: Immunomodulatory Agentsmentioning
confidence: 99%